Relationship Between Leptin and Neopterin Levels and Disease Activation Parameters in Patients With Rheumatoid Arthritis - Arif GÜLKESEN; Gürkan AKGÖL; Türkan TUNCER; Gül Ayden KAL; Selda TELO; Ahmet Kürşad POYRAZ; Arzu KAYA (Archives of Rheumatology, 2016)
Objectives: This study aims to determine serum leptin and neopterin levels in patients with rheumatoid arthritis (RA) and investigate the relationship between clinical and laboratory parameters of disease activity and radiographic progression. Patients and methods: The study included 33 RA patients (9 males, 24 females; mean age 52.5±12.3 years; range 29 to 75 years) and age- and sex-matched 24 healthy controls (11 males, 13 females, mean age 42.5±14.8; range 18 to 75). RA patients were divided into three groups based on Disease Activity Scores in 28 joints (DAS28) as low disease activity, moderate disease activity, and high disease activity groups. Of the patients, 13 (39.4%) had low disease activity (DAS28=2.6-3.2), 12 (36.4%) had moderate disease activity (DAS28=3.2-5.1), and eight (24.2%) had high disease activity (DAS28≥5.1). Results: Mean serum leptin and neopterin levels in the RA group were 23.98±18.88 ng/mL and 1.88±1.84 nmol/L, respectively. Mean serum leptin and neopterin levels in the control group were 19.40±13:42 ng/mL and 1.13±0.55 nmol/L, respectively. There was no statistically significant difference in the levels of serum leptin (p=0.674) and neopterin (p=0.078) between RA patients and control group. Serum leptin (p=0.574) and neopterin (p=0.921) levels in RA patients and control group showed no correlation with body mass index levels. Besides, there was no correlation between age and plasma leptin and neopterin levels and rheumatoid factor positivity, anti-cyclic citrullinated peptide antibodies, disease duration, erythrocyte sedimentation rate, and C-reactive protein levels in RA group. In RA patients, there was no correlation between serum leptin and neopterin levels and clinical and laboratory parameters indicating the disease activity. In RA patients, there was also no correlation between radiographic joint damage and serum leptin and neopterin levels. A positive correlation was shown in RA patients between disease duration and modified Larsen score (p=0.01). Conclusion: In our study, no correlation was detected between serum leptin and neopterin levels and disease activity parameters in RA patients. Therefore, leptin and neopterin levels may not be considered as beneficial inflammation parameters to be used in the diagnosis of RA and disease activation tracking.